THE OLVIOS, RETHIS AND INACHOS DRAINAGE SYSTEM EVOLUTION AND HUMAN ACTIVITIES INFLUNCE OF THEIR FUTURE EVOLUTION - Anagnostoudi, Th.; Papadopoulou, S.; Ktenas, D.; Gkadri, E.; Pyliotis, I.; Kokkidis, N.; Panagiotopoulos, V. (Bulletin of the Geological Society of Greece, 2010)
Olvios, Rethis and Inachos Rivers are multistory drainage systems that occur in Northern Peloponnesus, and at the present day they have and a reversed, North to South, flow element. Dervenios, Skoupeikos and Fonissa Rivers are the misfit streams of Olvios and revealed as juvenile streams and discharge to the Corinth gulf. Agiorgitikos River is the misfit stream of Rethis River and Seliandros River is the juvenile stream. Asopos, Nemeas and Rachiani Rives are the misfit streams of Inachos River and they also discharge to the Corinth gulf. Asopos River characterized as re-established stream. Physical factors such as tectonic regime (active and inactive faults), lithology, erosion and distance from the source influenced the three drainage systems evolution and could be influence them also in the future. The increase of human activities both in their southern parts and in the distal parts close to the coast could be change the physical evolution of the studied drainages, producing a new wind gap in the coastal area and a lake or a lagoon backwards of the coastal area, destroying villages and towns.